A Novel Low-Cost Machine for Evaluating Helmet Performance in Bike Accident Scenarios - Syed Mujahid Abbas; Haider Ali; Syed Aqib Ali Naqvi; Mohsin Iqbal; Hafiz Hamza Jabbar; Muhammad Azeem; Manzar Masud (Engineering Proceedings, 2023)
The increasing mortality rate in bike-related road accidents due to head injuries necessitates stronger helmets. This paper presents a cost-effective machine setup to evaluate helmet behavior during impacts. By employing unique methods to measure impact duration and post-impact energy absorption, this project eliminates the need for high-speed cameras. The results indicate that the developed machine enables scenario-based impact tests directly on helmets, providing valuable insights into collision effects. Validation confirms its effectiveness. The low-cost impact testing machine offers a practical solution for studying helmet performance and addressing the rising concerns surrounding bike accidents.